PARALLELIZATION OF LATTICE BOLTZMANN METHOD FOR CFD USING MESSAGE PASSING INTERFACE - Bashir, Shazia; Usman, Anila; Mumtaz, Yasir; Mahmoud, Khaled H.; Alsubaie, Abdullah S. A.; Bashir, Muhammad; İnç, Mustafa (Vinca Inst Nuclear Sci, 2022)
The lattice Boltzmann method has become a promising numerical technique and is now being considered as an alternative to the conventional CFD methods owing a possibility to simulate more complex geometries at relatively low computational costs. The simulations of complex and very fine resolution computational domains in CFD is challenging due to the lack of memory resources and long processing times, therefore parallel computing is being considered as a promising way to cope with this ever increasing mission of computational power. In this work parallelization of 2-D lattice Boltzmann model based CFD code using message passing interface was performed to increase speedup factor for parallel computing. Lattice Boltzmann approach based CFD code of a benchmark Lid driven cavity flow problem was parallelized using different message passing interface subroutines and made to run on a cluster system of processors. The time and speed up factor for execution of the benchmark problem was investigated. The results showed that these message passing communications have little influence on the performance of the parallel lattice Boltzmann method.
Keywords: lattice Boltzmann method; benchmark problem; message passing interface